CLINICAL, CULTURAL, ENDOCRINE AND THERAPEUTIC EVALUATION OF POSTPARTUM METRITIS IN SURTI BUFFALOES - PATIL, R D; PATEL, J A; DHAMI, A J; SARVAIYA, N P (The Indian Journal of Animal Reproduction, 2023)
This study was carried out on 40 postpartum metritic Surti buffaloes divided into five groups each of eightanimals. The study included use of four treatment lines and one control group, viz., Group I- Metronidazole (500mg) I/U for 5 days; Group 11-Ciprofloxacin (1500 mg) and Tinidazole (1800 mg) I/U for 5 days; Group Ill- Ciprofloxacin(1500 mg) and Tinidazole (1800 mg) I/U for5 days plus PGF20 25 mg i/m once on first day; Group IV-Ceftiofur(longacting) @ 6.6 mg/kg body wt subcutaneously once and Group V (control)- Normal saline I/U for 5 days. Theresponse to these therapeutic regimes was evaluated by comparing the clinical, cultural and endocrine changesbefore and after 5 days of treatment. The mean rectal temperature recorded after treatment was significantly(P
Keywords: Postpartum metritis; Buffaloes; Antibiotics; Hormones